Dementia mind, meaning, and the person - Hughes, Julian C.; Louw, Stephen J.; Sabat, Steven R. (Oxford : Oxford University Press, 2006)
This study juxtaposes philosophical analysis and clinical experience to present an overview of the issues surrounding dementia. It conveys a strong ethical message, arguing in favour of treating people with dementia with all the dignity they deserve as human beings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dementia -- Philosophy; Identity (Psychology); Self (Philosophy)